Feline Leishmaniasis Caused by Leishmania infantum: Parasite Sequencing, Seropositivity, and Clinical Characterization in an Endemic Area From Brazil - Santos, Nara Santos dos; Pinho, Flaviane Alves de; Hlavac, Nicole Regina Capacchi; Nunes, Talyta Lins; Almeida, Nádia Rossi; Solcà, Manuela Silva; Varjão, Bruno Milen; Portela, Ricardo Wagner; Rugani, Jeronimo Nunes; Rêgo, Felipe Dutra; Barrouin-Melo, Stella Maria; Soares, Rodrigo Pedro (Frontiers in Veterinary Science, 2021)
Zoonotic leishmaniasis caused by Leishmania infantum is a disease of One Health concern since human and animal cases and environmental damage are interconnected. L. infantum has a complex epidemiological cycle with multiple hosts, including mammals – humans, domestic and wild animals – and arthropod vectors. Knowledge on mammal infections in endemic areas is crucial for developing control strategies. This work aimed to detect and characterize L. infantum infection in domestic cats from areas where human and canine leishmaniasis cases occur. No cases of feline leishmaniasis (FeL) had been previously reported in those areas. Five municipalities from Bahia state were chosen, comprising 2,480.8 km2 with 1,103,866 inhabitants. Ninety domiciliated and/or sheltered cats underwent clinical examination and serology by a rapid reference test recommended by the Brazilian government. Cytology, PCR, and parasite DNA sequencing were performed in bone marrow samples. Rapid tests detected antibodies in 5.6% (5/90) of the cats. Leishmania infantum infection was confirmed in 7.8% (7/90) of the cats by PCR, sequencing, and parasite isolation. Three out of the five municipalities (60%) had infected cats, and PCR positivity varied from 6.9-29%. One cat was categorized as harbouring active L. infantum infection with amastigote forms in bone marrow smears. No clinical signs were present at the first clinical exam, but one month later the cat developed severe FeL. The cat isolate was grown in culture, typed and its DNA sequence having was homologous to the L. infantum reference strain (PP75). In conclusion, cats are potential hosts and may acquire L. infantum in endemic areas where canine and human cases occur. For cats, the need for surveillance, differential diagnosis and clinical care is highly recommended since a fast clinical progression of FeL developed in a subclinical animal. An accurate standardized immunodiagnostic assay for FeL is warranted.